Da prática da automedicação ao direito à saúde integral : vivências de um grupo de idosos da cidade de Passo Fundo/RS - Felkl, Rita de Cássia (2011)
The situation of the elderly in Brazil requires multidisciplinary studies that can point some ways in terms of building of a better quality of life and consequent respect and right to citizenship. In order of enlarging the comprehension of the causes of selfmedication experienced by a group of elderly in the city of Passo Fundo/RS, a survey was performed with older people in a social group with over 20 years of existence, managed by the municipality and because the University of Passo Fundo do numerous researches with the elderly. The sample was selected considering the indication of the coordination of DATI. The features of the sample participants were: they did not participate of any research before, aged 60 years or older, both sexes, independent and non-institutionalized elderly totaling 20 aged. Data collection was performed through a focus group. Data showed that: a)self-medication, although it was not admitted by the elderly, it is an usual practice. b) The most used medicines were analgesics and antiinflammatories, followed by muscle relaxants, polyvitaminics and drugs for treatment of influenza. c) The use of medicinal plants as tea is widely used with prescribed and non-prescribed medicines. d) The practice of self-medication is not a problem for the elderly. e) The media influence is a relevant factor that induces the purchase of medicines. f) The pharmacist, according to the elderly, has a significant role in the clarification about the use of medicines. g) The need of including, in the academic curriculum, disciplines related to human aging process. It is considered that through the analysis and critical discussion of this subject, it can contribute to a better understanding of the self-medication process seeking, this way, alternatives to this public health problem